2008
DOI: 10.1103/physrevd.78.032012
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive radiativeJ/ψdecays

Abstract: Using data taken with the CLEO-c detector at the Cornell Electron Storage Ring, we have investigated the direct photon momentum spectrum in the decay J/ψ(1S) → γgg, via the "tagged" process: e + e − → ψ(2S); ψ(2S)→ J/ψ π + π − ; J/ψ → γ+X. Including contributions from two-body radiative decay processes, we find the ratio of the inclusive direct photon branching fraction to that of the dominant three-gluon branching fraction (R γ = B(ggγ)/B(ggg)) to be R γ = 0.137 ± 0.001 ± 0.016 ± 0.004, where the errors shown… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In a subsequent work by the same group 25 , low Mn concentrations in κ carbides have been investigated which show absence of any kind of interaction between substitutional Mn atoms thereby indicating a random alloy system. A previous work further indicates the relevance of point defects such as C vacancies (treated in the dilute limit) for the thermodynamic stability of the relevant phases 22 . While these studies provided important insight into the structure and thermodynamics, none of them fully explained the above mentioned C reduction of κ carbides.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a subsequent work by the same group 25 , low Mn concentrations in κ carbides have been investigated which show absence of any kind of interaction between substitutional Mn atoms thereby indicating a random alloy system. A previous work further indicates the relevance of point defects such as C vacancies (treated in the dilute limit) for the thermodynamic stability of the relevant phases 22 . While these studies provided important insight into the structure and thermodynamics, none of them fully explained the above mentioned C reduction of κ carbides.…”
Section: Introductionmentioning
confidence: 81%
“…The main focus of previous theoretical studies has been on perfectly ordered κ carbides. In a previous investigation, DFT has been employed to compare the properties of Fe 3 Al-L1 2 and ordered Fe 3 AlC-E2 1 structures and to underline the role played by C 21,22 . These studies have shown that the addition of C atoms decreases the magnetic moment of the neighboring Fe atoms and yields a heat capacity and elastic constants of Fe 3 AlC-κ that are appreciably different from Fe 3 Al-L1 2 21 .…”
Section: Introductionmentioning
confidence: 99%
“…If the bottom reflection coefficient is known, the resulting attenuation length measurement can be stated with higher confidence, although it still represents an average over a large range of ice temperatures. For South Pole ice, experiments in this vein have yielded several results on the ice attenuation that indicate km-scale attenuation lengths in the upper km of ice [13][14][15][16].…”
Section: Deep Icecube Calibration Pulsermentioning
confidence: 99%
“…1. Solar Radio burst of Feb. 13,2011 On February 13, 2011, the Green Bank Solar Radio Burst Spectrometer detected a series of strong type II solar radio bursts in a broadband measurement spanning 10 MHz up to 1 GHz [18], as seen Fig. 15 (Bottom panels).…”
Section: B Thermal Noise Floormentioning
confidence: 99%
“…There are two processes with BR > 10%: η → ργ and the electromagnetic η → γγ, the latter along side the percent level η → γγ we will discuss in more detail. The large number of J/ψ events being collected in the nearfuture also presents the possibility of subpercent channels like J/ψ → η γ, as well as the percent-level but more complicated inclusive J/ψ → X h γ [45]. Predictions of X h + (µ + µ − ) decays require knowledge of hadronic transition form factors, and are more limited in precision compared to processes like η/η → (µ + µ − )γ where the better studied electromagnetic form factors are available.…”
mentioning
confidence: 99%